Persuadable how great leaders change their minds to change the world - Pittampalli, Al. (New York Harper Business, 2016)
As a leader, changing your mind has always been perceived as a weakness. Not anymore. In a world that?s changing faster than ever, successful leaders realize that a genuine willingness to change their own minds is the ultimate competitive advantage.
Includes bibliographical references (pages [213]-231) and index.
Keywords: Leadership